1992
DOI: 10.1007/bf00839139
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of sleep apnoea in workers exposed to organic solvents: implications for the diagnosis of organic solvent encephalopathy

Abstract: Among 51 patients referred for investigation of possible organic solvent encephalopathy 20 (39%) had pathological sleep apnoea [apnoea index (AI) greater than 5], compared with 5 of 16 house painters exposed to solvents (31%) who were screened for the disorder, and 1 of 18 (6%) age-matched controls. Twelve of the patients with AI greater than 5 were retested after 2 or more weeks without exposure to solvents, and showed a significant drop in AI. Likewise, significantly lower AI was seen in patients who were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
1
16
1
Order By: Relevance
“…This finding supports the theory that disturbances in the sleep-wake rhythm aggravate sleep apnea. This mechanism may also be the means for interpreting the observations made by Monstad et al (18), who documented the fall in an apnea index among 12 workers after the end of their exposing occupation.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This finding supports the theory that disturbances in the sleep-wake rhythm aggravate sleep apnea. This mechanism may also be the means for interpreting the observations made by Monstad et al (18), who documented the fall in an apnea index among 12 workers after the end of their exposing occupation.…”
Section: Discussionmentioning
confidence: 77%
“…The hypothesis that solvents induce sleep apnea is mainly based on three Scandinavian studies (17)(18)(19). In the first study, subjects who had been exposed to solvents were observed in a sleeping laboratory; they suffered from sleep apnea far more frequently than expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased fre quency of sleep apnea as compared to referents was demonstrated in a small group of workers with high exposure to trichloroethane [15]. There are several studies in which solventexposed patients with suspected or confirmed chronic toxic encephalopathy have been found to have higher frequencies of sleep apnea than referents [15][16][17].…”
Section: Organic Solvents and Sleep-disordered Breathingmentioning
confidence: 95%
“…Higher preva lences of sleeping problems and poor sleep quality have been reported among men occu pationally exposed to solvents [10][11][12][13], A case of sleep apnea was reported in a worker with high exposure to trichloroethane [ 14] and there are other studies in which occupational expo sure to organic solvents has been implicated as a possible cause of sleep apnea [15,16]. In an earlier study we have also found an increased prevalence of sleep apnea among men occupa tionally exposed to organic solvents [17].…”
Section: Occupational Exposure To Organic Solvents and Sleep-disordermentioning
confidence: 99%